Cover Image. (15th October 2020) - Wang, Qing; Chen, Jie; Zeng, Xianlin; Xin, Bin
Abstract : The cover image is based on the Research Article Distributed proximal‐gradient algorithms for nonsmooth convex optimization of second‐order multiagent systems by Qing Wang et al., https://doi.org/10.1002/rnc.5199 .